THE NEED FOR A CIVIL SERVICE REFORM IN NIGERIA - Ogbegie, Caleb Imuetinyan (My University, 2009)
This study will examine and surveys Nigeria's experience in fashioning out, vital reform in her Civil Service, over the years, with the aim of re-inventing the processes of governance to meet the ever increasing challenges in the business of governance. Further, it will look at the progress made over the years, the notable failures, successes, and likely solutions to some of the identified problems. Also, this work will highlight some of the challenges that have limited the success of the reforms. This work will also look at reforms in Nigeria, with respect to the New Public Management, and how the civil service in Nigeria, can modernize, using the ideas of the New Public Management.
Keywords: Public Administration; Civil Service; Reform; Corruption; fi=Public Administration|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|